ASSA14-11-04 Role of MiR-126 in development of hypertension MiR-126:a valuable predictor for hypertension. (1st December 2014) - Zhang, W; Nan, Y; Yu, L; Yang, J; Li, J
Abstract : Objective: Plasma microRNAs (miRNAs) have been recently reported to be sensitive and specific biomarkers of various tissue injuries and pathological conditions. MiR-126 plays an important role in maintaining endothelial cell homeostasis and vascular integrity. The goal of this study was to assess whether MiR-126 is good tool for the prognostication of hypertension. Methods: The plasma concentrations of miR-126and miR-499 were assessed among patients with pre-hypertension and hypertensionby a real-time reverse transcription-polymerase chain reaction using an artificial small RNA as an internal. Results: Plasma concentrations of miR-126 inpatients either with pre-hypertension (n = 22) or with hypertension (n = 36) were significantly lower than those in healthy controls (n = 15) (p < 0.01), and the concentrationsof hypertension group decreased more significantly. However, there was no difference in plasma concentrations of miR-499 among the study groups. Conclusions: Thesefindings suggest that miR-126 may be a useful biomarker for pre-hypertension and clinical hypertension.